FAKTOR YANG MEMPENGARUHI KEPUTUSAN SISWA SCHOTERS DALAM MEMILIH JEPANG SEBAGAI TUJUAN WISATA EDUKASI - Firmansyah, Angga; Wijaya, NMS.; Mahadewi, NPE. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024), 2024)
Educational tourism activities aim to provide learning experiences at the visited locations. Japan has become a favorite destination for students pursuing further studies. Combining tourism and education, Schoters emerges as a provider of preparatory courses for studying abroad. With the increasing number of students choosing Japan as an educational tourism destination, further research is needed to understand the factors influencing this decision. This study aims to identify the characteristics, the influencing factors, and the most dominant factor. The research was conducted by distributing questionnaires via Google Forms to Schoters students who chose Japan. The sample consisted of 100 respondents, determined using the Lameshow formula. This study used purposive sampling methods. Data were analyzed using the Likert scale and factor analysis, including validity and reliability tests. Data processing was carried out using the SPSS program version 29.0. The study identified four main factors: motivational factors, commercial-social factors, psychological factors, and natural factors. The results indicated that these factors influenced 59.7% of the students' decisions. The motivational factor was the dominant factor, influencing 28.957% out of the total 59.7%. This motivation stemmed from the students' internal drive to continue their studies in Japan and seek learning experiences beyond formal education.